2015
DOI: 10.1186/s13673-015-0028-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the value co-creation behavior of virtual customer environments using a hybrid expert-based DANP model in the bicycle industry

Abstract: Since 2008, soaring international oil prices and environmental awareness have pushed bicycle to be a green transport vehicle to reduce greenhouse gas emissions as a significant global trend. Consequently, Taiwan's bicycle industry earned the "bicycle kingdom" has entered a new peak period of demand under popular social trends of bicycling for health conscious and a healthy exercise tool; thus, to co-create value with customers to retain the reputation is important for Taiwan's bicycle industry. In Internet age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 68 publications
0
18
0
1
Order By: Relevance
“…Such data reduction facilitates the development of trust between customers and enterprises and opens direct channels of communication and product and service delivery. Similarly, knowledge-based data sharing facilitates the improved behavioral analysis of customers' data at a fine-grained level, thereby facilitating the delivery of personalized products and services to maximize the revenues and build long-term relationships (Chuang & Chen, 2015). Moreover, early data reduction improves the overall cost structure of enterprises by balancing the operational and optimization costs of business process models.…”
Section: Figure 5: Business Model Canvasmentioning
confidence: 99%
“…Such data reduction facilitates the development of trust between customers and enterprises and opens direct channels of communication and product and service delivery. Similarly, knowledge-based data sharing facilitates the improved behavioral analysis of customers' data at a fine-grained level, thereby facilitating the delivery of personalized products and services to maximize the revenues and build long-term relationships (Chuang & Chen, 2015). Moreover, early data reduction improves the overall cost structure of enterprises by balancing the operational and optimization costs of business process models.…”
Section: Figure 5: Business Model Canvasmentioning
confidence: 99%
“…From the study on Zara case, Royo-Vela and Casamassima [12] have demonstrated that the higher the level of participation in a virtual brand community, the higher the positive word-of-mouth advertising towards the brand around which the community is developed. Chuang and Chen [61] also did a research on the relationship between virtual customer participations and WOM. Additionally, members with high identification are more prone to contribute the organization with several desirable cooperative behaviors of helping other members and spreading good references [14,45,53,62].…”
Section: Wom and Repurchase Intentionmentioning
confidence: 99%
“…They indicated that exposure to public service ads directed at antichild abuse stimulates negative emotions (anger, sadness, fear and tension) leading to empathic responses influencing the decision to help. Rosenbaum and Massiah (2007) noted that customers usually recall difficulties that they encountered before and use it to form a strong sense of empathy and social responsibility to help other customers facing similar difficulties (Chuang and Chen, 2015). Bharti, Agrawal, and Sharma (2014) show that empathy is an important factor in influencing customers to participate in value co-creation activities.…”
Section: Hypotheses Development and Conceptual Modelmentioning
confidence: 99%